Alcohol Consumption Patterns and Sexual Risk Behavior among Female Sex Workers in two South Indian Communities - Anisa Heravian; Raja Solomon; Gopal Krishnan; CK Vasudevan; AK Krishnan; Thomas Osmand and Maria L. Ekstrand (Int J Drug Policy., 2012)
Background—HIV transmission in India is primarily heterosexual and there is a concentrated HIV epidemic among female sex workers (FSWs). Earlier reports demonstrate that many FSWs consume alcohol regularly before sexual encounters. This qualitative study is part of a larger quantitative study designed to assess alcohol consumption patterns among female sex workers and their association with sexual risk taking. Here we investigate the environmental influence, reasons for and consequences of consuming alcohol in the FSW population. Methods—Trained staff from two Non-Governmental Organizations in Andhra Pradesh and Kerala conducted semi-structured interviews with 63 FSWs in Chirala, Andhra Pradesh (n=35) and Calicut, Kerala (n=28) following extensive formative research, including social mapping and key informant interviews, to assess drinking patterns and sexual risk behaviors. Results—FSWs reported consuming alcohol in multiple contexts: sexual, social, mental health and self-medication. Alcohol consumption during sexual encounters with clients was usually forced, but some women drank voluntarily. Social drinking took place in public locations such as bars and in private locations including deserted buildings, roads and inside autorickshaws (motorcycle taxis). Consequences of alcohol consumption included failure to use condoms and to collect payments from clients, violence, legal problems, gastrointestinal side effects, economic loss and interference with family responsibilities. Conclusion—FSWs consume alcohol in multilevel contexts. Alcohol consumption during transactional sex is often forced and can lead to failure to use condoms. Social drinkers consume alcohol with other trusted FSWs for entertainment and to help cope with psychosocial stressors. There are multiple reasons for and consequences of alcohol consumption in this population and future interventions should target each specific aspect of alcohol use.